Implementasi Circular Economy 3R Model dan Literasi Keuangan Metode Participatory Learning Action Daerah 3T - Aloysius Kristianto (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2020)
The aim of this community service is to provide training and assistance in the circular economy 3R (Reduce-Reuse-Recycle) model, focused on community empowerment, by transforming waste into usable products with a sale value, both organic and inorganic. Education and assistance in financial literacy are also offered in the form of financial literacy. The approach used is Participatory Learning Action (PLA) through participatory observation, discussion, training and interviewing. The benefit of this community service initiative is that the community has an understanding of the proper disposal of waste, both organic and inorganic, which is reprocessed into organic and ecobrix liquid fertilizers as an effect of the recycling of plastic waste into basic furniture and can allow easy-to - understand notes on household finances.